2020
DOI: 10.1073/pnas.2019810117
|View full text |Cite
|
Sign up to set email alerts
|

Master curve of boosted diffusion for 10 catalytic enzymes

Abstract: Molecular agitation more rapid than thermal Brownian motion is reported for cellular environments, motor proteins, synthetic molecular motors, enzymes, and common chemical reactions, yet that chemical activity coupled to molecular motion contrasts with generations of accumulated knowledge about diffusion at equilibrium. To test the limits of this idea, a critical testbed is the mobility of catalytically active enzymes. Sentiment is divided about the reality of enhanced enzyme diffusion, with evidence for and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
53
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 59 publications
6
53
1
Order By: Relevance
“…We concluded that mobility during several common chemical reactions is more rapid than Brownian diffusion when the free energy release rate exceeds a threshold. This is in pleasing agreement with a master curve that reveals similar boosted mobility of catalytic enzymes, reconciling previous conflicting data in the literature (2). Boosted mobility was confirmed using an independent microfluidic gradient method.…”
supporting
confidence: 90%
“…We concluded that mobility during several common chemical reactions is more rapid than Brownian diffusion when the free energy release rate exceeds a threshold. This is in pleasing agreement with a master curve that reveals similar boosted mobility of catalytic enzymes, reconciling previous conflicting data in the literature (2). Boosted mobility was confirmed using an independent microfluidic gradient method.…”
supporting
confidence: 90%
“…Recently, this capability of chemical/kinetic energy conversion was also extended to many other types of active enzymes, such as urease, catalase, DNA polymerase, and hexokinase. These enzymes were shown to diffuse faster when catalyzing their substrates in the solution [4][5][6][7][8][9][10][11][12]. The mechanism of the molecular level enhanced diffusion of single enzyme is still under debate.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it reports a strong positive correlation between enhanced diffusion and the change in Gibbs free energy (as well as the Michaelis-Menten reaction rate) from FCS also supported by dynamic light scattering experiments. Such a correlation, whose robustness is further tested by tuning the reaction rate with both temperature and pH, may explain why the effect has been observed for enzymes catalyzing both endothermic as well as exothermic reactions and provides a path toward a satisfactory mechanistic framework, grounded in thermodynamics, of the origin of enhanced diffusion (4). It also unequivocally predicts where future enzymes are expected to fall on the master curve based on the intrinsic properties of the reactions they catalyze.…”
mentioning
confidence: 88%
“…Equally surprising is the observation, counter to any macroscopic hydrodynamic expectation, that catalytic proteins (enzymes) exhibit enhanced diffusion upon catalysis (4). The latter is the focus of "Master curve of boosted diffusion for 10 catalytic enzymes" by Jee et al (4), where the effect of diffusion enhancement of 10 enzymes is probed by fluorescence correlation spectroscopy (FCS) (Fig. 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation